Heat transfer of 3D printed heat sinks under no flow bypass conditions - Noor Muhammad Noor Khalid (2018)
This study experimentally investigated complex heat sink designs fabricated by Selective Laser Melting (SLM) under no flow bypass with air as the working fluid. The heat sinks consist of pin fin arrays with circular, parabola and NACA4412 (with an angle of attack of 0°) geometries. In addition, heat sinks with lattice structure designs were also fabricated. The lattice structures consist of the Rhombi-Octet unit cell design and cell sizes of 5 mm, 7 mm, 10 mm, and 12 mm were investigated. The heat sink designs are of consistent volume. The results show that the Nusselt number (Nu) increases with increasing Reynolds number (Re) for all heat sinks tested. Friction factor also decreases as Re increases in lattice structures tested. In addition, Nu correlations for the new lattice structures were derived using the permeability and ligament diameter of the unit cell. It is also shown that the lattice structures have higher heat transfer coefficients than the pin fin heat sinks but at the cost of larger pressure drop. As compared to metallic commercial foams, the lattice structures performed better with higher heat transfer performance and lower friction factor and the 7 mm unit cell is shown to be the best performing heat sink.